1996
DOI: 10.1108/03090599610150282
|View full text |Cite
|
Sign up to set email alerts
|

Competence development ‐ a challenge for HRM professionals: core competences of organizations as guidelines for the development of employees

Abstract: Explains the theory on the core competences of the organization and the competences of individual employees. Looks at the management style in competence-based organizations and the way in which a competence-based human resource management (HRM) system can help in achieving the organization's objectives, as well as examining competence management and empowerment. A concrete application of a competencebased HRM system in the petro-chemicals industry illustrates the task of linking an organization's core competen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 3 publications
3
36
0
2
Order By: Relevance
“…A total of eight competency domains were identified: appearance and attitude, physical fitness, customeroriented skills and company loyalty, knowledge of foreign cultures and languages, emotional intelligence, skills for in-flight services, past work experience, and interpersonal skills. These factors included not only skills or knowledge but also personalities or attitudes that support the pursuit of individual development (Bergenhenegouwen et al, 1996;Sandwith, 1993;Spencer & Spencer, 1993). For example, the results suggested that cabin crews should behave elegantly and make proper gestures.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of eight competency domains were identified: appearance and attitude, physical fitness, customeroriented skills and company loyalty, knowledge of foreign cultures and languages, emotional intelligence, skills for in-flight services, past work experience, and interpersonal skills. These factors included not only skills or knowledge but also personalities or attitudes that support the pursuit of individual development (Bergenhenegouwen et al, 1996;Sandwith, 1993;Spencer & Spencer, 1993). For example, the results suggested that cabin crews should behave elegantly and make proper gestures.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The previous literature has explained that a competency comprises two distinct elements: innate traits and acquired skills (Bergenhenegouwen et al, 1996). As presented in Figure 2, the bottom of the pyramid, which describes hidden competencies, shows that the structure of a competency includes innate human characteristics, such as self-image, motivation, effort, enthusiasm, values, standards, and moral criteria.…”
Section: Components Of Competency and Competency Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Boog (1991, como citado em Campos et al, 2008 O conceito de competência está ligado à qualidade de quem é capaz de apreciar e resolver certo assunto, fazer determinada coisa; significa capacidade, habilidade, aptidão e idoneidade. Bergenhenegouwen (1996) Competências individuais dizem respeito a características fundamentais da personalidade que são inerentes às ações das pessoas em relação a todos os tipos de tarefas e situações; especialidades e habilidades; motivos e qualidades. Cheetam e Chivers, (2005, como citado em De Coi et al, 2007 Competência é o desempenho efetivo dentro de um domínio/contexto em diferentes níveis de proficiência.…”
Section: Brandão E Borgesandrade (2007)unclassified